The Administration of Intradialytic Parenteral Nutrition Does Not Affect the Anemia Status of Chronic Kidney Disease Patients Undergoing Hemodialysis - Hertanto, Decsa Medika; Nurwidda, Arvi Dian Prasetia; Tjempakasari, Artaria; Widodo, Widodo; Pranawa, Pranawa (Indonesian Journal of Kidney and Hypertension, 2024)
Background: Hemodialysis (HD) patients are susceptible to malnutrition, and there is a close relationship between malnutrition and the incidence of anemia. Parenteral nutrition plays a role in treating malnutrition. Objective: This study aims to determine the effect of parenteral nutrition on anemia in HD patients. Methods: Quasi-experimental research which is part of the nutritional research tree at the Hemodialysis Unit of RSUP Dr. Soetomo Surabaya for 3 months. A total of 45 malnourished CKD patients (SGA B & C) undergoing routine HD were included in this study (n=26 received regular diet & education, n=17 received regular diet, education and intradialytic parenteral nutrition, and n=2 dropped out of school due to blood transfusion). Measurements of body mass index (BMI), hemoglobin (Hb), serum iron (SI), and total iron binding capacity (TIBC) were carried out before and 8 weeks after therapy. Between groups used the Mann-Whitney test, while pre and post used the Wilcoxon matched-pairs sign rank test. Results: The treatment group was older than the control group. There was no difference in duration of HD between groups. Intradialytic parenteral nutrition had no effect on BMI (24.71±3.939 vs 24.71±4.026; p=0.3802), Hb (9.746±1.309 vs 9.162±1.960; p= 0.3525), SI (62.33±34.74 vs. 53.78±24.89; p=0.3594), and TIBC (242.8±119.0 vs. 197.3±43, 65; p=0.4258). Conclusion: In HD patients, intradialytic parenteral nutrition for 8 weeks did not affect Hb, SI and TIBC levels. Long-term observations with larger samples are needed to confirm these findings.